2012
DOI: 10.1111/j.1537-2995.2012.03670.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood ordering from the operating room: turnaround time as a quality indicator

Abstract: Many of the surveyed institutions do not monitor stat RBC issue TAT as a quality indicator. This study serves as a starting point for establishing a benchmark for TAT for issuing RBCs from the blood bank to ORs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The 8-min timeline for a blood issue was comparable with the other studies, which found an issue TAT of 6–21 min. [1315] The authors believe that due to the gravity of the task (final check before release), there is hardly any scope for further reducing this time. Irrespective of whether a manual or an automated system was used, the issue time has averaged around 5–7 min in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The 8-min timeline for a blood issue was comparable with the other studies, which found an issue TAT of 6–21 min. [1315] The authors believe that due to the gravity of the task (final check before release), there is hardly any scope for further reducing this time. Irrespective of whether a manual or an automated system was used, the issue time has averaged around 5–7 min in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect should be contemplated by the protocol algorithm of each hospital center. 1,2,42,43 The use of MOH protocols has been shown to be useful for facilitating rapid transfusion of a sufficient volume of blood products, and such protocols are also cost-effective (lesser general use of products). Massive obstetric hemorrhage protocols moreover improve the communication lines referred to the request for transfusion and transport from the blood bank to the place where the blood is needed.…”
Section: Massive Transfusion Protocols In Mohmentioning
confidence: 99%
“…The time table for issuing blood emergently depends on whether type-specific, crossmatched RBC can be provided within an acceptable turnaround time[28], based on the diagnostic antibody screen results (Table 1). We have developed a standardized MTP for women with an emergent need for blood transfusion, including those whose antibody screen evaluation was positive or unknown upon admission.…”
Section: Massive Transfusion Protocol For Postpartum Hemorrhagementioning
confidence: 99%